Capillary Transit Time Heterogeneity and Flow-Metabolism Coupling after Traumatic Brain Injury. Issue 10 (October 2014) - Østergaard, Leif; Engedal, Thorbjørn S; Aamand, Rasmus; Mikkelsen, Ronni; Iversen, Nina K; Anzabi, Maryam; Næss-Schmidt, Erhard T; Drasbek, Kim R; Bay, Vibeke; Blicher, Jakob U; Tietze, Anna; Mikkelsen, Irene K; et al.
Most patients who die after traumatic brain injury (TBI) show evidence of ischemic brain damage. Nevertheless, it has proven difficult to demonstrate cerebral ischemia in TBI patients. After TBI, both global and localized changes in cerebral blood flow (CBF) are observed, depending on the extent of diffuse brain swelling and the size and location of contusions and hematoma. These changes vary considerably over time, with most TBI patients showing reduced CBF during the first 12hours after injury, then hyperperfusion, and in some patients vasospasms before CBF eventually normalizes. This apparent neurovascular uncoupling has been ascribed to mitochondrial dysfunction, hindered oxygen diffusion into tissue, or microthrombosis. Capillary compression by astrocytic endfeet swelling is observed in biopsies acquired from TBI patients. In animal models, elevated intracranial pressure compresses capillaries, causing redistribution of capillary flows into patterns argued to cause functional shunting of oxygenated blood through the capillary bed. We used a biophysical model of oxygen transport in tissue to examine how capillary flow disturbances may contribute to the profound changes in CBF after TBI. The analysis suggests that elevated capillary transit time heterogeneity can cause critical reductions in oxygen availability in the absence of 'classic' ischemia. We discuss diagnostic and therapeutic consequences of these predictions.